Cinefluoroscopy for assessment of mechanical heart valves with suspected dysfunction - Derda, Anselm A.; Marquardt, Marvin M.; Martens, Andreas; Mirena, Elion; Vogel-Claussen, Jens; Kempf, Tibor; Haverich, Axel; Bauersachs, Johann; Napp, L. Christian (Frontiers in Cardiovascular Medicine, 2022)
Background Mechanical heart valves are preferred prosthesis types in many, especially younger patients who need surgical valve replacement. Although echocardiography is most frequently used for prosthesis assessment during follow-up, ultrasound artifacts usually preclude precise investigation of prosthesis function. Cinefluoroscopy is a simple and effective method to analyze and quantify opening and closing of prosthesis leaflets, but requires careful visualization of the valve using optimal viewing angles. Here we investigated the quality of cinefluoroscopy studies in clinical routine and their suitability for quantitative analysis of prosthesis function. Methods and Results We retrospectively identified 94 patients with 118 cinefluoroscopies, performed by 31 different investigators in one tertiary center from 2012 to 2021. Of 150 mechanical heart valves (98% dual leaflet prostheses), 87 were aortic (58%), 53 mitral (34%), 7 tricuspid (5%), and 5 pulmonary (3%) valve prostheses, respectively. Cinefluoroscopies were categorized by their suitability to quantitatively assess opening and closing angles. Visualization of valve function was “sufficient” in 23%, “suboptimal” in 46%, and “unsuitable” in 31% of cases. Conclusions In clinical routine, only one fourth of cinefluoroscopy studies allows for complete assessment of leaflet motion of mechanical heart valves. Although this may be in part due to varying experience of operators, the high number of unsuitable studies suggests that optimal viewing angles may not be achievable in all patients. Further research is required to investigate standard viewing angles and anatomy after mechanical heart valve implantation, to improve quality of cinefluoroscopy studies and reduce radiation exposure for patients and operators.